Who controls the past? - Penny English (Internet Archaeology, 2013)
This collection of articles presents a series of snapshots of different aspects of the regulatory framework and practice of metal detecting (and related issues). Each shines a spotlight on a different context but underlying all of them is the same fundamental question. Although the focus of heritage law and management is on tangible property, i.e. objects and places, the debate always leads us back to the intangible and seemingly insoluble question of who should have the right to control access to the past. These articles speak with a variety of voices, some more forcibly than others. The resulting kaleidoscope of viewpoints illuminates the challenge of reaching a workable management regime for the archaeological heritage, at times highlighting points of convergence, at others the unbridgeable gulf between different communities of interest, all claiming a stake in the past.